ChemInform Abstract: Smart Polymeric Nanoparticles as Emerging Tools for Imaging — The Parallel Evolution of Materials. Issue 20 (April 2016) - Papadimitriou, Sofia A.; Salinas, Yolanda; Resmini, Marina
Abstract: Review: [62 refs.